Analisis Gaya Hidup Hedonisme di Kalangan Mahasiswa (Studi Kasus: Mahasiswa Ilmu Filsafat Universitas Pembangunan Panca Budi Medan) - Danny Abrianto; Vinna Salwa Arani (AR-RASYID : Jurnal Pendidikan Agama Islam, 2021)
This research aims to describe the Hedonistic Lifestyle Among Students (Case Study: Student of Philosophy at the Panca Budi Development University). This study uses a descriptive qualitative method approach based on the type of field research (field research). The results of this study are students of this group prefer a life with fun. The pleasures of the world take priority over the intellectual. His lifestyle is always extravagant, always spending time playing games such as hanging out in cafes, shopping, joining high-class social communities, and so on. Students of this group also always follow trends and follow developments of globalization such as fashion and technology. Then the factors that influence the student's lifestyle are influenced by internal factors and external factors. The forms of hedonistic student lifestyle such as shopping addiction, the trend of buying branded goods, hanging out in luxury places.